Use of Social Media in BSI Marketing Smart Agent BSI KC Palangkaraya Diponegoro Palangkaraya City Region - Nur Alisa; Ajahari, Ajahari; Andrea Geovani (Dinasti Publisher, 2025)
BSI Smart Agent is a solution to enhance the accessibility of banking services, particularly for communities living in remote areas or far from bank branches and ATMs. The potential of BSI Smart Agent in PalangkaRaya is significant, given its vast area of 2,853.00 km² and the need for inclusive financial services. This study aims to examine the utilization of social media in marketing BSI Smart Agent and to identify the challenges in optimizing this marketing strategy. A qualitative method with a field research approach was used, and data were collected through observation and in-depth interviews. Sampling was conducted using purposive sampling, involving BSI KC Palangka Raya Diponegoro employees, including the Branch Operation and Service Manager and RSE Digital. The results showed that BSI KC Palangka Raya uses WhatsApp Status on employees’ accounts and official social media platforms like Instagram and Facebook to market BSI Smart Agent. However, social media marketing challenges include fraud and customer misunderstandings. Therefore, BSI KC Palangka Raya prioritizes face-to-face interactions to ensure clear communication and build customer trust.